A critical review on In Vivo and Ex Vivo models for the investigation of Helicobacter pylori infection - Patil, Shwetlaxmi; Yu, Songmin; Jobby, Renitta; Ravichandran, Vinothkannan; Sarkar, Sohinee (Frontiers in Cellular and Infection Microbiology, 2025)
Helicobacter pylori is a stomach-dwelling bacterium with a crude global prevalence of nearly 45% in adults and 35% in children and adolescents. Chronic H. pylori infection and the resulting inflammation are major causes of gastritis, peptic ulcer disease and gastric cancer. Since its discovery in 1982, various animal models have been proposed to recreate the specific pathophysiological interactions between H. pylori and the human host. These infection models have been instrumental in dissecting the key drivers of H. pylori colonization, persistence and mediators of host immune responses. However, a comprehensive understanding of the molecular triggers for malignant transformation of the gastric mucosa is still lacking. Vaccine development in this area has stalled, as promising candidates identified through animal studies have failed in advanced human clinical trials. Currently, H. pylori eradication is heavily reliant on different antimicrobial agents. As with other bacterial pathogens, the growing antimicrobial resistance in H. pylori remains a major challenge, making eradication therapy increasingly complex and prolonged, over time. Recent drug approvals have mostly been for newer combinations of conventional antibiotics and proton pump inhibitors. Thus, the development of novel treatments and innovative models are crucial for advancing the drug development pipeline. This review encompasses the development and recent advances in animal and non-animal models of H. pylori gastric infection and its applications in investigating novel therapeutics and vaccine candidates.